Sanctions on South Africa: What Did They Do? - Levy, Philip I (American Economic Review, 1999)
This paper considers the economic sanctions that were applied in the mid-1980s to pressure the South African government to end apartheid. It asks what role those sanctions played in the eventual demise of the apartheid regime and concludes that the role was probably very small. An alternative explanation for the regime change is offered: the communist bloc combined to bring about the change. If one is to argue for the efficacy of sanctions, two key obstacles are their limited economic impact and the substantial lag between the imposition of sanctions and the political change. Since sanctions preceded the change of government, it is impossible to rule them out as a determinant. However, their principal effect was probably psychological. The implication is that the South African case should not serve as the lone major instance of effective sanctions. Keywords: Sanctions, South Africa, Political Economy, Trade J.E.L. classification: F14 2 Sanctions on South Africa: What did th...